Modern Innovative Ways to Transfer Information from Teacher to Student when Studying Human Anatomy, Operative Surgery and Topographic Anatomy on Pirogov's Interactive Anatomical Table (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The doctor's knowledge of the individual anatomy from the standpoint of the three-dimensional topography of the organ structures of each patient is becoming a leading task on the way to solving the issues of high-quality care provided by modern medical practice. The interactive anatomical atlas of 3D images "Pirogov" allows you to transfer the study of disciplines of anatomical nature to a new mainstream of computational anatomy, or anatomia in silico.